2011
DOI: 10.1038/ng.902
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing supports a de novo mutational paradigm for schizophrenia

Abstract: Despite high heritability, a large fraction of cases with schizophrenia do not have a family history of the disease (sporadic cases). Here, we examine the possibility that rare de novo protein-altering mutations contribute to the genetic component of schizophrenia by sequencing the exome of 53 sporadic cases, 22 unaffected controls and their parents. We identified 40 de novo mutations in 27 patients affecting 40 genes including a potentially disruptive mutation in DGCR2, a gene removed Users may view, print, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
328
0
25

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(369 citation statements)
references
References 35 publications
16
328
0
25
Order By: Relevance
“…4,22,26,39 Vissers et al 4 showed that de novo point mutations could be linked to disease in 7 out of 10 patients with intellectual disability, indicating that these mutations may explain the large majority of the genetic burden. These remarkable findings in intellectual disability have recently been replicated in sporadic forms of autism 39 and schizophrenia, 5 indicating that de novo mutations may explain a considerable proportion of the sporadic forms of common neurodevelopmental disorders. 4,40 Note that, as for the other strategies, variants prioritized in this way are more likely to be causative for disease, but de novo occurrence in itself is not sufficient evidence, and follow-up studies are required to identify recurrence or functional proof of pathogenicity.…”
Section: Gene Identification Strategies For Exome Sequencing C Gilissmentioning
confidence: 90%
“…4,22,26,39 Vissers et al 4 showed that de novo point mutations could be linked to disease in 7 out of 10 patients with intellectual disability, indicating that these mutations may explain the large majority of the genetic burden. These remarkable findings in intellectual disability have recently been replicated in sporadic forms of autism 39 and schizophrenia, 5 indicating that de novo mutations may explain a considerable proportion of the sporadic forms of common neurodevelopmental disorders. 4,40 Note that, as for the other strategies, variants prioritized in this way are more likely to be causative for disease, but de novo occurrence in itself is not sufficient evidence, and follow-up studies are required to identify recurrence or functional proof of pathogenicity.…”
Section: Gene Identification Strategies For Exome Sequencing C Gilissmentioning
confidence: 90%
“…Gbx2 is a homeobox transcriptional factor that has been shown to regulate various aspects of neural stem cell differentiation (44) and may contribute to the reported effects of GCs on differentiation of distinct neuroprogenitors (11)(12)(13). No role for phospholipase C-related protein (Plcl2) in neurodevelopment or GC action has been reported, although Plcl2 was identified in exome sequencing analysis as one of 40 genes with protein coding sequence variations in schizophrenia patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…9 Since that publication, the study has generated exome sequence data for most participants. 21 The National Human Genome Research Institute's Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%